Financial risk taking : an introduction to the psychology of trading and behavioural finance - Elvin, Mike (Wiley trading series., 2004)
In Financial Risk Taking, trader and psychologist Mike Elvin explores the complex relationship between human behaviour patterns and the markets, offering the reader a context in which to assess their own strengths and weaknesses as investors. The book offers an apposite and uncomplicated system of skills development in the form of competences and competencies that can be applied anywhere along the continuum from casual investor to full-time day trader.